2016
DOI: 10.1038/srep37405
|View full text |Cite
|
Sign up to set email alerts
|

Timing predictability enhances regularity encoding in the human subcortical auditory pathway

Abstract: The encoding of temporal regularities is a critical property of the auditory system, as short-term neural representations of environmental statistics serve to auditory object formation and detection of potentially relevant novel stimuli. A putative neural mechanism underlying regularity encoding is repetition suppression, the reduction of neural activity to repeated stimulation. Although repetitive stimulation per se has shown to reduce auditory neural activity in animal cortical and subcortical levels and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 59 publications
3
20
0
Order By: Relevance
“…When expected self-generated sensory feedback is modified, suppression is reduced (e.g., Knolle et al, 2013b). Differences in the processing of self-generated and externally generated input have also been observed in middle latency responses preceding the N1 (i. e., approximately at 27-33 ms after sound onset; Baess et al, 2009), which are sensitive to the temporal regularity of a stimulus (Gorina-Careta et al, 2016;Leung et al, 2013). The P50 (even though not directly examined in the context of button press tasks) was also found to be sensitive to temporal stimulus predictability White and Yee, 2006).…”
Section: Introductionmentioning
confidence: 93%
“…When expected self-generated sensory feedback is modified, suppression is reduced (e.g., Knolle et al, 2013b). Differences in the processing of self-generated and externally generated input have also been observed in middle latency responses preceding the N1 (i. e., approximately at 27-33 ms after sound onset; Baess et al, 2009), which are sensitive to the temporal regularity of a stimulus (Gorina-Careta et al, 2016;Leung et al, 2013). The P50 (even though not directly examined in the context of button press tasks) was also found to be sensitive to temporal stimulus predictability White and Yee, 2006).…”
Section: Introductionmentioning
confidence: 93%
“…These experiences include long-term language experience (Krishnan, Xu, Gandour, & Cariani, 2005; Krizman, Marian, Shook, Skoe, & Kraus, 2012; Krizman, Skoe, Marian, & Kraus, 2014; Xie, Reetzke, & Chandrasekaran, 2017), musical training (Musacchia, Sams, Skoe, & Kraus, 2007; Wong, Skoe, Russo, Dees, & Kraus, 2007), short-term auditory training (Song, Skoe, Wong, & Kraus, 2008; Xie et al, 2017), online context (Lau, Wong & Chandrasekaran, 2016), and stimulus probability and FFR timing (Gorina-Careta, Zarnowiec, Costa-Faidella & Escera, 2016; Shiga, Althen, Cornella, Zarnowiec, Yabe & Escera, 2015; Slabu, Grimm & Escera, 2012). Following this line of research, recent studies have documented a more faithful subcortical encoding of lexical tones (e.g., Mandarin tones) in native speakers of tonal languages (e.g., Chinese), relative to native speakers of languages that are not tonal (e.g., English) (Krishnan et al, 2010; Krishnan, Gandour, Bidelman, & Swaminathan, 2009; Krishnan et al, 2005; Xie et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been shown that the FFR can also act as a diagnostic tool for mild traumatic brain injuries 18 , 19 . Importantly, the FFR exhibits flexibility at different time scales and can be modified by changes in the stimulus dynamics 20 22 and by short 23 25 and long-term experiences 26 , 27 . Short-term interventions, such as auditory or linguistic training, enhance the neural encoding of the F0 which accompanies improvements in perceptual skills 25 , 28 .…”
Section: Introductionmentioning
confidence: 99%